Behaviour of solute transport phenomenon from rainfed sweet corn field in tropical climate - Iqbal, Mazhar (2020)
Solute transport from agricultural fields is the main cause of non-point contamination, resulting in degradation of surface and groundwater due to runoff and deep percolation. It varies significantly among agricultural fields of different climates. The amount and duration of rainfall occurrence in the tropical climate is of great importance in controlling solute movement from agricultural fields. The heavy rainfall in tropical climate results in the solute loss to increase manifold as compared to arid and semi-arid climate. Therefore, assessment of water and solute balance in rainfed conditions is essential for the efficient use of water and fertiliser in increasing productivity. The study intended to assess the water and solute dynamics from a sweet corn field under tropical rainfed conditions using the HYDRUS-1D numerical model. The intensive field investigations were carried out to explore the water and solute losses in a sweet corn field for two growing seasons (Feb.-May and Sep.-Nov. 2018) under the rainfed conditions at the Malaysian Agricultural Research and Development Institute (MARDI), Malaysia. The water and solute balance components were observed using modern devices integrated with data loggers in real field conditions and the empirical relationships between solute concentrations and EC were developed. Then HYDRUS-1D numerical analysis was performed to simulate soil water balance in the sweet corn field. The HYDRUS-1D numerical model was also used to simulate solute transport dynamics in the field. The observed soil water content and solute concentrations were used for calibration and validation of the model. Finally, the AquaCrop simulations of crop growth were performed to predict crop yield using the data obtained from the intensive field experiments. The empirical relationships between the observed NPK concentrations and EC were developed during the first season using polynomial regression analysis. Based on the developed empirical equations, the NPK concentrations were determined and compared with observed concentrations during the second season. The average R2 values for NPK were 0.91, 0.97, and 0.98 (first season) and 0.97, 0.95 and 0.98 (second season). The empirical relationship is an important and easier way to know the NPK status in the soil at any given time during the crop growing seasons and could be helpful in the efficient use of fertiliser. The total water inputs during the first and second seasons were 75.8 cm and 79.7 cm, respectively. HYDRUS-1D simulation results of evapotranspiration (ET) accounted for 40.7% and 33.1% of total water input during the first and second seasons, respectively. Surface runoff accounted for 41.0% (first season) and 28.6% (second season). Water leaching accounted for 10.6% and 26.8% of total water input during both seasons, respectively. The total NPK input to sweet corn was 120:60:60 kg/ha for both seasons. The nitrogen (N) surface runoff loss accounted for 35.3% and 22.2% of total nitrogen input during the first and second seasons, respectively. The N leaching loss at 60 cm depth accounted for 4.0% (first season) and 18.5% (second season). The crop N uptake was 37.5% (first season) and 24.9% (second season). The phosphorus (TP) losses were negligible. The simulated amounts of K lost through runoff and leaching were 43.1% and 17.0% (first season), 34.1% and 38.6% (second season). The K uptake accounted for 32.1% and 21.4% of total K input during the first and second seasons, respectively. NPK losses through surface runoff and leaching were dominating pathways. Overall, the HYDRUS-1D simulation results of soil water fluxes and NPK concentrations were found in good agreement with observed data. The simulated total biomass of 11.2 ton/ha and 8.8 ton/ha were obtained using the AquaCrop model during the first and second seasons, respectively. The total yields were 5.4 ton/ha (first season) and 4.2 ton/ha (second season). The simulated results show higher water productivity (WPET) 1.69 kg/m3 during the first season as compared to 1.58 kg/m3 during the second season. The AquaCrrop simulation results matched the observed results well. The overall simulation results validate the HYDRUS-1D as an effective tool for improved water and fertiliser use and AquaCrop to simulate the crop growth in the tropical climate.